Examining Green Hotels in Northeastern India: The Role of Consumer Satisfaction in Mediating Green Marketing and Intentions to Revisit - Shivam Sharma, Abhishek Kar, Uday Pratap Singh (Journal of Informatics Education and Research, 2025)
This study explores the connection between green marketing practices and guests' intentions to revisit green hotels in Northeastern India, focusing on the mediating effect of consumer satisfaction. With sustainability becoming a priority in the hospitality sector, green hotels that implement eco-friendly practices are emerging as a successful model in the region. States like Assam, Meghalaya, Arunachal Pradesh, and Sikkim known are known for their rich biodiversity and natural beauty, are inclined to adopt sustainable tourism. This research examines how green marketing strategies—such as eco-friendly initiatives, waste reduction, and energy efficiency—impact guest satisfaction and their likelihood of returning.